Bis [4-hydroxy-N'-(4-methoxy-2-oxidobenzylidene-O2) benzohydrazidato-2O, N'] cadmium (II) dimethyl sulfoxide disolvate - Mohd Lair, N.; Ng, S.W.; Ali, Hapipah Mohd (2009)
The metal atom in the title compound, [Cd(C15H13N2O4)2]·2C2H6OS, is twice O,N,O'-chelated by two symmetry-related Schiff base ligands to define a trans-N2O4 octahedral geometry. Each anion occupies meridional sites of the octahedron; the metal atom lies on a special position of site symmetry 2. The dimethyl sulfoxide molecule is a hydrogen-bond acceptor to the -NH- unit, and O-H...O hydrogen bonds link molecules into a supramolecular chain.